Agricultural Information Needs and their Fulfillment as Perceived by the Farmers in Changing Agricultural Scenario in Maharashtra - Chandrakant, Awatade Sudarshan; Ghosh , Souvik; Singandhupe, R B (Indian Journal of Extension Education, 2017)
Nowadays, there are numerous extension agencies that are providing agricultural extension services to the farmers in the  form of information and service support but the results are still not satisfactory in accordance with need fulfillment of  farmers in the context of changing agricultural scenario in Maharashtra state. Hence, present study was aimed to assess  diverse information needs of farmers from agricultural extension system. It was conducted in Yavatmal district of  Maharashtra that included a random sample of 80 farmers, 20 each from four randomly selected villages representing two  blocks. The present study reveals that soil, weather and climate, nutrient management, market prices and income  generating activities are the prime needed aspects related to agricultural inputs with mean need perception score more than  3.5 on four point continuum scale followed by livelihood diversification, agricultural marketing, seeds, agri entrepreneurship, subsidies, plant protection material, weed management, pest and disease management and crop  diversification had mean need perception score more than average (>2.5) on four point continuum scale. However, the  most of the information needs were fulfilled partially as opined by the farmers. The low perception of felt needs of the  farmers on post harvest management and higher need perception on marketing aspects clearly indicated the fact of  unwillingness and ignorance on value addition, quality control, etc. of agricultural produce and preference of marketing  the produce as quickly as possible. However, the farmers expressed their interest in capacity building aspects viz. diversification of livelihood, agri- entrepreneurship and crop diversification by growing high value crops.
Keywords: Agricultural extension system; farmers' information needs; need perception; need fulfillment; current agricultural changes